Irreversible electroporation combined with chemotherapy and PD-1/PD-L1 blockade enhanced antitumor immunity for locally advanced pancreatic cancer - Ma, Yangyang; Xing, Yanli; Li, Hongmei; Yuan, Ting; Liang, Bing; Li, Rongrong; Li, Jianyu; Li, Zhonghai; Li, Shuying; Niu, Lizhi (Frontiers in Immunology, 2023)
Background Irreversible electroporation (IRE) is a novel local tumor ablation approach with the potential to stimulate an antitumor immune response. However, it is not effective in preventing distant metastasis in isolation. This study aimed to compare the potential of augmenting the antitumor immune response in patients with locally advanced pancreatic cancer (LAPC) who underwent IRE combined with chemotherapy and PD-1/PD-L1 blockade with those who underwent IRE combined with chemotherapy. Methods A retrospective review was conducted on LAPC patients treated either with IRE in combination with chemotherapy and PD-1/PD-L1 blockade (group A) or with IRE with chemotherapy alone (group B) from July 2015 to June 2021. The primary outcomes were overall survival (OS) and progression-free survival (PFS), with immune responses and adverse events serving as secondary endpoints. Risk factors for OS and PFS were identified using univariate and multivariate analyses. Results A total of 103 patients were included in the final analysis, comprising 25 in group A and 78 in group B. The median duration of follow-up was 18.2 months (3.0–38.6 months). Group A patients demonstrated improved survival compared to group B (median OS: 23.6 vs. 19.4 months, p = 0.001; median PFS: 18.2 vs. 14.7 months, p = 0.022). The data suggest a robust immune response in group A, while adverse events related to the treatment were similar in both groups. The multivariate analysis identified the combination of IRE, chemotherapy, and PD-1/PD-L1 blockade as an independent prognostic factor for OS and PFS. Conclusion The addition of PD-1/PD-L1 blockade to the regimen of IRE combined with chemotherapy enhanced antitumor immunity and extended survival in LAPC patients.